2019
DOI: 10.1016/j.clon.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicine in Cancer Treatment – How is it Practised in the East and the West?

Abstract: Chinese medicine therapies in cancer treatment are very common in the East. Although it is usually classified as a form of complementary and alternative therapy in the West, Chinese medicine is an independent medical profession in Hong Kong and mainland China. It has a different perspective in understanding health and diseases compared with Western medicine. In oncology practice, whereas Western medicine focuses on direct tumour eradication by surgery, radiation therapy and systemic therapies, Chinese medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…The exact molecular mechanism for the functional role of Tai Chi was not explored in the CHD patients after PCI. The possible side effects of Tai Chi were not investigated, although most reports showed that Tai Chi could reduce most side effects of various diseases (Murley et al, 2019;So et al, 2019). According to our experiences, there is a difference in learning Tai Chi between males and females, but the issue was not explored in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…The exact molecular mechanism for the functional role of Tai Chi was not explored in the CHD patients after PCI. The possible side effects of Tai Chi were not investigated, although most reports showed that Tai Chi could reduce most side effects of various diseases (Murley et al, 2019;So et al, 2019). According to our experiences, there is a difference in learning Tai Chi between males and females, but the issue was not explored in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…In oncology practice, Chinese medicine is commonly used to reduce side-effects from chemotherapy or radiation therapy, to aid recovery after an operation, to palliate symptoms and to address survivorship issues. 18 ASCO Endorsement of the SIO Clinical Practice Guideline indicated that acupressure and acupuncture are recommended for reducing chemotherapy-induced nausea and vomiting. 19,20 Currently, there are a lot of trials that have reported that acupuncture treats cancer patients in order to palliate symptoms.…”
Section: Dovepressmentioning
confidence: 99%
“…Chinese Traditional Medicine is often used as complementary or supportive medicine for the treatment of oncological patients 7 . It has been reported that these MHs, as well as dietary supplements, are responsible for 26.8% of DILI hospitalizations, 8 but it is not clear how many of these patients self‐prescribed MHs 7 .…”
mentioning
confidence: 99%
“…Chinese Traditional Medicine is often used as complementary or supportive medicine for the treatment of oncological patients 7 . It has been reported that these MHs, as well as dietary supplements, are responsible for 26.8% of DILI hospitalizations, 8 but it is not clear how many of these patients self‐prescribed MHs 7 . So and colleagues reported that their preliminary data indicate that 25% of patients with solid tumours were prescribed Chinese Traditional Medicines in addition to conventional treatments 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation